Entrepreneurship and Vocational Education and Career Intentions of Students in Tertiary Institutions in Ogun State, Nigeria - AKINSANYA, Omolade, 0.; OLANIYI , Olusegun S.; OSHIYADI, Peter .O. (International Journal of Educational Management, 2025)
The undesirable career intentions among students have contributed to a phenomenon which has led to a constantly growing graduates’ unemployment rates in the labour market. The study was conducted to determine the influence of entrepreneurship and vocational education on career intentions of students in tertiary institutions in Ogun State, Nigeria. Descriptive research design was employed in the study. A sample of 607 tertiary education students in their final year entrepreneurship and vocational education courses were randomly selected in three tertiary institutions in Ogun State. A questionnaire tagged ’Students’ Career Intentions and Perception of Entrepreneurship and Vocational Education Questionnaire (SPEVEO)’ was used to collect data for the study. The instrument was validated first and the reliability coefficient was 0. 78. This ensured the instrument was reliable for the study. Five research questions were raised and answered using frequency counts, percentages and ordinal logistics regression as methods of data analysis. Findings also revealed that paid employment was the main career intention of tertiary education students (63.2%). Entrepreneurship and vocational education significantly influenced career intentions of tertiary education students (I) = 229.254, p < .05. The study recommends that Entrepreneurship and Vocational Education Development Centres (EVEDC) should be given more priority by government in all public tertiary institutions to provide financial supports and other essential materials needed towards achievement of career intention for self-employability.